Moderasi Beragama dalam Perspektif Tafsir Quraish Shihab dan Implementasinya dalam Pendidikan Agama Islam - Ageng Malisi; Nikco Ariyanto; Raffi Anugrah; Ika Kurnia Sofiani (Jurnal Teologi Islam, 2026)
This study aims to analyze the concept of religious moderation in Tafsir Al-Mishbah by M. Quraish Shihab and its implementation in Islamic Religious Education. The study uses a qualitative approach with the type of library research. The primary data source of the study is Tafsir Al-Mishbah by M. Quraish Shihab, while secondary data sources include books, journals, and relevant previous research. The data collection technique is carried out through documentation studies, while data analysis uses content analysis methods. The results of the study indicate that religious moderation according to M. Quraish Shihab is based on the concept of wasathiyah which emphasizes an attitude of balance, justice, tolerance, deliberation, respect for diversity, and rejection of extreme attitudes in religion. These values have strong relevance to Islamic Religious Education and can be implemented through integration in learning objectives, development of teaching materials, teacher role models, the use of discussion and deliberation methods, and strengthening the moderate character of students. Thus, M. Quraish Shihab's thoughts can be the basis for developing moderate, inclusive Islamic Religious Education, and oriented towards the formation of the character of students who are able to live harmoniously in a pluralistic society.